Polyester resin composition for injection molding, and injection molded article
A combination of poly(3-hydroxyalkanoate), aliphatic aromatic polyester resin, and layered clay mineral improves low-temperature impact strength in injection molded articles, addressing the limitations of existing polyester resin compositions.
Patent Information
- Application Number
- JP2020158119
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-23
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-09-23
AI Technical Summary
Existing polyester resin compositions for injection molding, particularly those containing poly(3-hydroxyalkanoate), lack sufficient low-temperature impact strength, limiting their use in cold environments.
A combination of poly(3-hydroxyalkanoate) resin, aliphatic aromatic polyester resin, and layered clay mineral, with specific weight ratios and components, enhances low-temperature impact strength.
The composition achieves excellent low-temperature impact strength and moldability, enabling the production of injection molded articles suitable for cold conditions.
Smart Images

Figure 0007606304000001 
Figure 0007606304000002 
Figure 0007606304000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester resin composition for injection molding and an injection molded article, and in particular to a polyester resin composition for injection molding that contains a large amount of poly(3-hydroxyalkanoate), which has excellent biodegradability, and has excellent impact strength at low temperatures, and an injection molded article. [Background technology]
[0002] In recent years, environmental problems caused by waste plastics have been highlighted, and the realization of a recycling-based society on a global scale is eagerly awaited. In this environment, biodegradable plastics that are decomposed into water and carbon dioxide by the action of microorganisms after use have been attracting attention. In addition, in the composting of food waste carried out in Europe and other places, garbage bags that can be thrown into the compost together with the garbage are desired. Biodegradable plastics include poly(3-hydroxyalkanoate) (hereinafter sometimes referred to as P3HA), polycaprolactone, polybutylene adipate terephthalate, polybutylene succinate adipate, polybutylene succinate, and the like, and the development of compositions and molded bodies using these biodegradable resins is being promoted. In particular, among these biodegradable resins, P3HA has the highest biodegradability, and various biodegradation processes such as composting and anaerobic decomposition at around room temperature are possible. Therefore, from the viewpoint of biodegradability, it is preferable to incorporate a large amount of P3HA alone or in a resin composition with other biodegradable resins.
[0003] For example, Patent Document 1 exemplifies an injection molded article of an aliphatic polyester resin composition containing polyhydroxyalkanoate (3-hydroxybutyrate-co-3-hydroxyhexanoate, abbreviated as PHBH) and a filler such as pentaerythritol or talc as a crystallization nucleating agent. However, there is room for improvement in terms of impact strength at low temperatures (5°C or less, particularly in the temperature range of 0°C or less), and the applications are limited.
[0004] Patent Document 2 discloses an aliphatic polyester resin composition having excellent moldability and impact resistance, which contains an aliphatic polyester resin containing repeating units derived from an aliphatic diol and an aliphatic dicarboxylic acid, a polyhydroxyalkanoate, and an inorganic filler. However, there is room for improvement in terms of low-temperature impact strength. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2015 / 052876 [Patent Document 2] JP 2019-178206 A Summary of the Invention [Problem to be solved by the invention]
[0006] In view of the above, the present invention is the result of extensive research and an object of the present invention to provide a polyester resin composition for injection molding having excellent low-temperature impact strength and an injection-molded article thereof. [Means for solving the problem]
[0007] As a result of intensive research aimed at solving the above-mentioned problems, the inventors discovered that low-temperature impact strength is significantly improved in a composition containing a poly(3-hydroxyalkanoate) resin (P3HA), an aliphatic aromatic polyester resin and a layered clay mineral, and thus completed the present invention. That is, in order to solve the above problems, the polyester resin composition of the present invention comprises a polyester resin represented by the following general formula (1):
[0008] [ka]
[0009] (However, R is C n H 2n+1and n is an alkyl group represented by the formula: n is an integer of 1 or more and 15 or less. The polyester resin composition for injection molding contains a poly(3-hydroxyalkanoate) resin (A) having a repeating unit represented by the formula: (A) an aliphatic aromatic polyester resin (B) and a layered clay mineral (C), characterized in that the proportion of the resin (A) is 55 to 75% by weight and the proportion of the resin (B) is 25 to 45% by weight relative to the total of the resins (A) and (B), and the content of the clay mineral (C) is 5 to 35 parts by weight when the total of the resins (A) and (B) is 100 parts by weight.
[0010] In addition, the poly(3-hydroxyalkanoate) resin (A) is preferably at least one selected from the group consisting of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), poly(3-hydroxybutyrate) (P3HB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate), and poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate).
[0011] The aliphatic aromatic polyester resin (B) is preferably at least one selected from the group consisting of polybutylene adipate terephthalate resins, polybutylene sebacate terephthalate resins, and polybutylene succinate terephthalate resins.
[0012] The layered clay mineral (C) is preferably at least one selected from the group consisting of smectite, mica, talc, pyroferrite, vermiculite, chlorite, kaolinite and serpentine. The present invention is also characterized by being an injection molded article containing the polyester resin composition for injection molding. Effect of the Invention
[0013] According to the present invention, it is possible to provide a polyester resin composition for injection molding, which has excellent low-temperature impact strength, and an injection-molded article thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] An embodiment of the polyester resin composition for injection molding of the present invention will be described below, but the present invention is not limited thereto.
[0015] The polyester resin composition for injection molding according to the present invention comprises, as a resin component, a compound represented by the following general formula (1): [-CHR-CH2-CO-O-] (1) (However, R is C n H 2n+1 where n is an integer of 1 to 15.) and an aliphatic aromatic polyester resin (B), and further a layered clay mineral (C).
[0016] The poly(3-hydroxyalkanoate) resin (P3HA) used in the present invention is a polyester resin produced from a microorganism.
[0017] The microorganism that produces P3HA is not particularly limited as long as it has the ability to produce P3HAs. For example, examples of bacteria that produce copolymers of hydroxybutyrate and other hydroxyalkanoates include Aeromonas caviae, which produces copolymers having 3-hydroxybutyrate and 3-hydroxyvalerate as monomer units (hereinafter abbreviated as "PHBV") and poly(3-hydroxybutyrate-co-3-hydroxyhexanoate (hereinafter abbreviated as "PHBH"), and Alcaligenes eutrophus, which produces poly(3-hydroxybutyrate-co-4-hydroxybutyrate). In particular, with regard to PHBH, Alcaligenes eutrophus AC32 (FERM), into which genes of PHA synthesis enzymes have been introduced, have been used to increase the productivity of PHBH. BP-6038) (J. Bateriol., 179, p. 4821-4830 (1997)) are more preferred, and microbial cells in which PHBH has been accumulated by culturing these microorganisms under appropriate conditions are used.
[0018] The weight average molecular weight of the P3HA used in the present invention is preferably 50,000 to 3,000,000, more preferably 100,000 to 1,500,000, from the viewpoint of the balance between moldability and physical properties. It is further preferably 150,000 to 1,000,000, and particularly preferably 200,000 to 600,000. The weight average molecular weight here refers to a value measured from the polystyrene equivalent molecular weight distribution using gel permeation chromatography (GPC) using a chloroform solution. If the weight average molecular weight is less than 50,000, the molded product may be too brittle, and if it exceeds 3,000,000, the melt viscosity may be too high, making injection molding difficult.
[0019] The P3HA used in the present invention is preferably one consisting of a repeating unit in which n of the alkyl group (R) in the general formula (1) is 1, or one consisting of a repeating unit in which n is 1 and at least one of repeating units in which n is 2, 3, 5, and 7, and more preferably one consisting of a repeating unit in which n is 1 and a repeating unit in which n is 3. Specific examples of P3HA include poly(3-hydroxybutyrate) (abbreviation: P3HB), poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (abbreviation: PHBH), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (abbreviation: PHBV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (abbreviation: P3HB4HB), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate), poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate), and the like. Among these, P3HB, PHBH, PHBV, and P3HB4HB are easily produced industrially.
[0020] Among these, PHBH, which is composed of a repeating unit in which n in the alkyl group (R) is 1 and a repeating unit in which n is 3 in the general formula (1) in the above, is preferred from the viewpoints that by changing the composition ratio of the repeating units, it is possible to change the melting point, the degree of crystallinity, and physical properties such as Young's modulus and heat resistance, and it is possible to impart physical properties between polypropylene and polyethylene, and that it is a plastic that is easy to produce industrially and is physically useful as described above. A specific method for producing PHBH is described in, for example, International Publication No. 2010 / 013483. In addition, examples of commercially available PHBH products include Kaneka Biodegradable Polymer PHBH) (registered trademark) from Kaneka Corporation.
[0021] In addition, from the viewpoint of the balance between flexibility and strength, the composition ratio of the repeating unit of PHBH is preferably 80 / 20 to 99 / 1 (mol / mol), more preferably 85 / 15 to 97 / 3 (mol / mol), further preferably 90 / 10 to 97 / 3 (mol / mol), and particularly preferably 93 / 7 to 96 / 4 (mol / mol). If the composition ratio of the repeating unit of PHBH is less than 80 / 20, solidification may be slow and the molding cycle may be short. If it is more than 99 / 1, the moldable temperature may exceed the decomposition temperature, making it impossible to mold.
[0022] The aliphatic-aromatic polyester resin (B) used in the present invention is a polyester resin containing one or more dicarboxylic acid units selected from the group consisting of aliphatic dicarboxylic acid units and aromatic dicarboxylic acid units, and one or more diol units selected from the group consisting of aliphatic diol units and aromatic diol units, and is a polyester resin having both aliphatic units and aromatic units.
[0023] The aliphatic aromatic polyester resin (B) used in the present invention is preferably a polybutylene adipate terephthalate resin, a polybutylene sebacate terephthalate resin, or a polybutylene succinate terephthalate resin, and particularly preferably a polybutylene adipate terephthalate resin (PBAT). Polybutylene adipate terephthalate resin (PBAT) refers to a random copolymer of 1,4-butanediol, adipic acid, and terephthalic acid. Among them, PBAT obtained by reacting (a) a mixture consisting mainly of 35 to 95 mol % of adipic acid or its ester-forming derivative or a mixture thereof, and 5 to 65 mol % of terephthalic acid or its ester-forming derivative or a mixture thereof (the sum of the individual mol % is 100 mol %) with (b) a mixture containing butanediol (wherein the molar ratio of (a) to (b) is 0.4:1 to 1.5:1), as described in JP-A-10-508640, etc., is preferred. Commercially available PBAT products include "Ecoflex" (registered trademark) manufactured by BASF.
[0024] The mixing ratio of the P3HA (A) and the aliphatic aromatic polyester resin (B) in the polyester of the present invention is 55 to 75% by weight of the resin (A) and 25 to 45% by weight of the resin (B) relative to the total weight of the resins (A) and (B) in order to obtain excellent low-temperature strength of the molded product.
[0025] The layered clay mineral (C) used in the present invention is a mineral mainly composed of layered silicate, and can improve heat resistance and processability. In particular, the layered clay mineral (C) is preferably one or more selected from the group consisting of smectite, mica, talc, pyroferrite, vermiculite, chlorite, kaolinite, and serpentine, in that it is easy to improve processability. In terms of versatility, mica, talc, and kaolinite are preferred, and talc is particularly preferred.
[0026] Examples of the mica include wet-ground mica and dry-ground mica, and specific examples include mica manufactured by Yamaguchi Mica Co., Ltd. and Keiwa Rozai Co., Ltd.
[0027] Examples of the talc include general-purpose talc and surface-treated talc. Specific examples include "Microace" (registered trademark) from Nippon Talc Co., Ltd., "Talcan Powder" (registered trademark) from Hayashi Kasei Co., Ltd., and talc manufactured by Takehara Chemical Industry Co., Ltd. and Maruo Calcium Co., Ltd.
[0028] Examples of the kaolinite include dry kaolin, calcined kaolin, wet kaolin, etc., and specific examples include "TRANSLINK" (registered trademark), "ASP" (registered trademark), "SANTINTONE" (registered trademark), and "ULTREX" (registered trademark) manufactured by Hayashi Kasei Corporation, and kaolinite manufactured by Keiwa Rozai Co., Ltd.
[0029] The content of the layered clay mineral (C) is preferably 5 to 35 parts by weight, more preferably 6 to 25 parts by weight, and particularly preferably 7 to 15 parts by weight, when the total of the poly(3-hydroxyalkanoate) resin (A) and the aliphatic aromatic polyester resin (B) is 100 parts by weight. If the layered clay mineral (C) is less than 5 parts by weight, solidification may be slow and moldability may be poor. On the other hand, if the layered clay mineral (C) is more than 35 parts by weight, the melt viscosity may be too high and moldability may be poor.
[0030] Furthermore, to the resin composition of the present invention, one or more of the following secondary additives may be added, provided the effects of the present invention are not impaired: fillers other than the layered clay minerals used as ordinary additives, colorants such as pigments and dyes, odor absorbents such as activated carbon and zeolite, fragrances such as vanillin and dextrin, antioxidants, weather resistance improvers, ultraviolet absorbers, crystallization nucleating agents, lubricants, release agents, water repellents, antibacterial agents, sliding property improvers, and other secondary additives.
[0031] Examples of the crystallization nucleating agent include pentaerythritol, orotic acid, aspartame, cyanuric acid, glycine, zinc phenylphosphonate, and boron nitride. Among them, pentaerythritol is preferred because it is particularly effective in promoting the crystallization of poly(3-hydroxyalkanoate) resin. The amount of the crystallization nucleating agent used is not particularly limited, but is preferably 0.1 to 5 parts by weight, more preferably 0.5 to 3 parts by weight, and even more preferably 0.7 to 1.5 parts by weight, relative to 100 parts by weight of poly(3-hydroxyalkanoate) resin. The crystallization nucleating agent may be used alone or in combination of two or more kinds, and the mixing ratio can be appropriately adjusted depending on the purpose.
[0032] Examples of the lubricant include behenamide, oleamide, erucamide, stearamide, palmitamide, N-stearylbehenamide, N-stearylerucamide, ethylenebisstearamide, ethylenebisoleamide, ethylenebiserucamide, ethylenebislauramide, ethylenebiscapricamide, p-phenylenebisstearamide, and polycondensates of ethylenediamine, stearic acid, and sebacic acid. Among them, behenamide and erucamide are preferred because of their particularly excellent lubricant effect on poly(3-hydroxyalkanoate)-based resins. The amount of the lubricant used is not particularly limited, but is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, and even more preferably 0.1 to 1.5 parts by weight, relative to 100 parts by weight of poly(3-hydroxyalkanoate)-based resin. In addition, the lubricant may be used alone or in combination of two or more kinds, and the mixing ratio can be appropriately adjusted depending on the purpose.
[0033] Examples of the plasticizer include glycerin ester compounds, citrate compounds, sebacic acid ester compounds, adipate compounds, polyether ester compounds, benzoic acid ester compounds, phthalic acid ester compounds, isosorbide ester compounds, polycaprolactone compounds, and dibasic acid ester compounds. Among them, glycerin ester compounds, citrate compounds, sebacic acid ester compounds, and dibasic acid ester compounds are preferred because of their particularly excellent plasticizing effect on poly(3-hydroxyalkanoate) resins. Examples of the glycerin ester compounds include glycerin diacetomonolaurate and the like. Examples of the citrate compounds include acetyl tributyl citrate and the like. Examples of the sebacic acid ester compounds include dibutyl sebacate and the like. Examples of the dibasic acid ester compounds include benzyl methyl diethylene glycol adipate and the like. The amount of the plasticizer used is not particularly limited, but is preferably 1 to 20 parts by weight, more preferably 2 to 15 parts by weight, and even more preferably 3 to 10 parts by weight, per 100 parts by weight of the total of the poly(3-hydroxyalkanoate) resin and the polylactic acid. In addition, the plasticizer may be used alone or in combination of two or more kinds, and the mixing ratio can be appropriately adjusted depending on the purpose. Next, one embodiment of the method for producing the polyester resin composition for injection molding of the present invention will be described, but the present invention is not limited thereto.
[0034] The resin composition of the present invention can be produced using a known kneader such as a single screw extruder, a twin screw extruder, or a Banbury mixer. Of these, a twin screw extruder is preferred as the kneader because it can disperse the layered clay mineral (C) in the resin without applying excessive shear to the resin. As for the setting conditions of the kneader, it is preferred to set the cylinder temperature to 180°C or less because it can suppress the thermal decomposition of P3HA. When each component is fed to the kneader, it may be added all at once, or some of the components may be kneaded and then the remaining components may be kneaded. Since the layered clay mineral (C) may damage the resin, it is preferable to add the layered clay mineral (C) by using a side feed or the like after melt-kneading the resin components. As a molding method when processing the polyester resin composition for injection molding of the present invention into an injection molded article, a general injection molding method can be used, for example, an injection molding method generally used when molding a thermoplastic resin, as well as a gas-assisted molding method, an injection compression molding method, etc. can be used. In-mold molding, gas press molding, two-color molding, sandwich molding, PUSH-PULL, SCORIM, etc. can also be used, but the injection molding method usable in the present invention is not limited to the above methods, and specific conditions may be set appropriately. Applications of the injection molded articles obtained by the present invention are not particularly limited, and examples thereof include tableware such as plates, cups, cutlery, etc., coffee capsules, agricultural materials, OA parts, home appliance parts, automotive parts, toys, daily necessities such as boxes and containers, stationery such as ballpoint pens, mechanical pencils, rulers, etc., molded articles such as bottles, caps, lids, extruded sheets and films, irregular extrusion products, etc. In addition, the injection molded articles obtained by the present invention have seawater degradability because the resin component is mainly composed of poly(3-hydroxyalkanoate)-based resin, and therefore can solve environmental problems caused by ocean dumping of plastics. EXAMPLES
[0035] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples in any way. (Ingredients used) The raw materials used in the present examples and comparative examples are summarized in Table 1.
[0036] [Table 1]
[0037] The evaluation methods carried out in the examples and comparative examples are described below.
[0038] (Mold releasability) Using the injection molding conditions described below, a three-plate, pin-gate, single-cavity coffee capsule mold with a thickness of 0.4 mm was used. The cooling time was shortened, and the minimum cooling time during which no release problems occurred was measured, and the releasability was evaluated based on the following criteria. ◎: Less than 10 seconds ○: 10 to less than 20 seconds △: 20 to 25 seconds ×: 25 seconds or more
[0039] (Appearance evaluation) The appearance of the molded article obtained by injection molding as described below was visually inspected and judged based on the following criteria. ○: Good appearance ×: If one or more molding defects, either burrs or flow marks, are found
[0040] (surface impact test) From the 8cm x 8cm x 1mm plate obtained by injection molding as described below, 4cm x 4cm x 1mm plates were cut out and left to cure for one day in thermostatic chambers at 23℃ and 0℃. After that, a 300g impact core was dropped from a height of 50cm and 10 test pieces were tested to calculate the non-destructive rate using the following formula. Non-destructive rate (%) = Number of unbroken test pieces (pieces) / Total number of test pieces (pieces) x 100
[0041] <Example 1> (Preparation of PHBH Blend) Using a 75L Super Mixer manufactured by Kawata Corporation, 10 kg of PHBH, 100 g of PETL, 50 g of BA, and 50 g of EA were mixed at 300 rpm for 3 minutes to obtain a PHBH blend.
[0042] (Compounding using a twin-screw extruder) A Toshiba Machine TEM26SS (L / D=60) was used with the screw configuration shown in Table 2, and the screw speed was set to 100 rpm. The PHBH blend was fed from the base of the screw at 7.14 kg / hr, and simultaneously, PBAT was fed from the base of the screw at 3.0 kg / hr, and talc was side-fed at 1.0 kg / hr. The strands were solidified by passing them through a water tank filled with 45°C hot water, and then cut into pellets by a pelletizer.
[0043] [Table 2]
[0044] (Acquisition of injection molded body) Using a 8cm x 8cm x 1mm plate mold and a Toyo Machinery Metal injection molding machine Si-30V, the nozzle / T1 / T2 / T3 = 155 / 145 / 135 / 125°C and the mold temperature was 35°C, and a plate-shaped molded body measuring 8cm x 8cm x 1mm was obtained. The obtained injection molded article was subjected to an appearance evaluation and a surface impact test, and the results are shown in Table 3. Furthermore, the mold releasability was evaluated, and the results are shown in Table 3.
[0045] <Example 2> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed at 6.12 kg / hr, the PBAT was fed at 4.0 kg / hr, and talc was fed at 1.0 kg / hr from the side feed through the screw base. The appearance, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0046] <Example 3> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed at 7.14 kg / hr, the PBAT was fed at 3.0 kg / hr, and talc was fed at 2.0 kg / hr from the side feed through the screw base. The appearance, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0047] <Example 4> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed at 6.12 kg / hr, PBAT at 4.0 kg / hr, and talc was fed at 2.0 kg / hr from the side feed of the screw. Appearance evaluation, surface impact test, and demolding property were evaluated, and the results are shown in Table 3.
[0048] <Example 5> An experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed from the base of the screw at 7.14 kg / hr, PBAT was fed at 3.0 kg / hr, and talc was fed from the side feed at 3.0 kg / hr. Appearance evaluation, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0049] <Comparative Example 1> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed from the base of the screw at 10.20 kg / hr and PBAT and talc were not fed. Appearance evaluation, surface impact test, and demolding property were evaluated. The results are shown in Table 3.
[0050] <Comparative Example 2> From the base of the screw, the PHBH blend was fed at 8.16 kg / hr and PBAT was fed at 2.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding property were evaluated. The results are shown in Table 3.
[0051] <Comparative Example 3> From the base of the screw, the PHBH blend was fed at 7.14 kg / hr and PBAT was fed at 3.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding property were evaluated. The results are shown in Table 3.
[0052] <Comparative Example 4> From the base of the screw, the PHBH blend was fed at 6.12 kg / hr and PBAT was fed at 4.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding property were evaluated. The results are shown in Table 3.
[0053] <Comparative Example 5> From the base of the screw, the PHBH blend was fed at 8.16 kg / hr and PBSA was fed at 2.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding properties were evaluated. The results are shown in Table 3.
[0054] <Comparative Example 6> From the base of the screw, the PHBH blend was fed at 7.14 kg / hr and PBSA was fed at 3.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding properties were evaluated. The results are shown in Table 3.
[0055] <Comparative Example 7> From the base of the screw, the PHBH blend was fed at 6.12 kg / hr and PBSA was fed at 4.0 kg / hr. Except for not feeding talc, an experiment was carried out in the same manner as in Example 1. Appearance evaluation, surface impact test, and demolding properties were evaluated. The results are shown in Table 3.
[0056] <Comparative Example 8> An experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed from the base of the screw at 7.14 kg / hr, PBAT was fed at 3.0 kg / hr, and talc was fed from the side feed at 4.0 kg / hr. Appearance evaluation, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0057] <Comparative Example 9> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed from the base of the screw at 7.14 kg / hr, PBSA was fed at 3.0 kg / hr, and talc was fed from the side feed at 1.0 kg / hr. The appearance, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0058] <Comparative Example 10> The experiment was carried out in the same manner as in Example 1, except that the PHBH blend was fed at 6.12 kg / hr, the PBSA was fed at 4.0 kg / hr, and talc was fed at 1.0 kg / hr from the side feed through the screw base. The appearance, surface impact test, and demolding properties were evaluated, and the results are shown in Table 3.
[0059] [Table 3]
[0060] Table 3 shows the results of various evaluations of resin compositions containing the contents of resin (A) and resin (B) relative to the total of poly(3-hydroxyalkanoate) resin (A) and aliphatic aromatic polyester (B), and the content (parts by weight) of layered clay mineral (C) when the total of resin (A) and resin (B) is 100 parts by weight. These results show that, compared to Comparative Examples 1 to 10, Examples 1 to 5 have superior low-temperature impact strength, and have short cooling times for demolding, resulting in high productivity and enabling the production of injection-molded articles with good appearance.
Claims
1. The following general formula (1) 【Chemistry 1】 (However, R is C n H 2n+1 and n is an integer of 1 to 15), an aliphatic aromatic polyester resin (B), and a layered clay mineral (C), The ratio of the resin (A) is 55 to 75% by weight, and the ratio of the resin (B) is 25 to 45% by weight, based on the total weight of the resin (A) and the resin (B); A polyester-based resin composition for injection molding, in which the clay mineral (C) is 5 to 30 parts by weight when the total of the resin (A) and the resin (B) is 100 parts by weight (however, this does not include a composition containing 30 parts by weight or more and 60 parts by weight or less of polylactic acid out of a total of 100 parts by weight of polylactic acid, the resin (A), and the resin (B)).
2. The polyester resin composition for injection molding according to claim 1, characterized in that the poly(3-hydroxyalkanoate)-based resin (A) is at least one selected from the group consisting of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (PHBH), poly(3-hydroxybutyrate) (P3HB), poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV), poly(3-hydroxybutyrate-co-4-hydroxybutyrate) (P3HB4HB), poly(3-hydroxybutyrate-co-3-hydroxyoctanoate), and poly(3-hydroxybutyrate-co-3-hydroxyoctadecanoate).
3. 3. The polyester resin composition for injection molding according to claim 1, wherein the aliphatic aromatic polyester resin (B) is at least one selected from the group consisting of polybutylene adipate terephthalate resins, polybutylene sebacate terephthalate resins, and polybutylene succinate terephthalate resins.
4. The polyester resin composition for injection molding according to any one of claims 1 to 3, characterized in that the layered clay mineral (C) is at least one selected from the group consisting of smectite, mica, talc, pyroferrite, vermiculite, chlorite, kaolinite and serpentine.
5. An injection molded article comprising the polyester resin composition for injection molding according to any one of claims 1 to 4.
Citation Information
Patent Citations
biodegradable polyester mixture
JP2008527120A
Polymer blend with improved rheology and improved unnotched impact strength
JP2012062490A
Molding, sheet and container
JP2019178206A
Aliphatic polyester resin composition and aliphatic polyester resin molded body
WO2015052876A1
Biodegradable polyester resin composition and molded body formed from said resin composition
WO2017138392A1
